ASSESSING THE ASSESSMENT AND EVALUATION PROCESS AT PYP: A CASE STUDY - Taj Mohammad; Soada Idris (Universitas Kuningan, 2018)
The present study is designed to assess the assessment and evaluation process at Preparatory Year Program, Najran University. The research aims to assess the formative and summative assessment process at PYP and offer recommendations to further strengthen the summative/formative assessment and evaluation process. In order to assess the teachers opinion, the researchers circulated the questionnaire to forty participants and finally, twenty questionnaires given serious attention were selected as samples of this study. The research had a detailed analysis and discussion on the statements of the questionnaire as well as detailed analysis and discussion on the responses of interview. An overall analysis of assessment and evaluation process affirms that summative assessments (question papers) are well designed and closely observe learning objectives and learning outcomes except a few modifications. Keywords: continuous assessment, evaluation, formative assessment, summative assessment